Prevalence of neurocysticercosis among people with epilepsy in rural areas of Burkina Faso - Millogo, Athanase (Epilepsia, 2012)
PURPOSE: To estimate the lifetime prevalence of neurocysticercosis (NCC) associated epilepsy and the proportion of NCC among people with epilepsy in three Burkina Faso villages. METHODS: Three villages were selected to represent three types of pig-rearing methods: 1) Batondo where pigs are left to roam; 2) Pabré where pigs are mostly tethered or penned, and 3) Nyonyogo where the majority of residents are Muslim and few pigs are raised. In Batondo and Nyonyogo, all concessions (a group of several households) were included. Half of the concessions in Pabré were randomly chosen. All households of selected concessions were included, and one person per household was randomly selected for epilepsy screening and serological testing for cysticercosis. Self-reported cases of epilepsy were also examined and confirmed cases included in analyses other than the estimate of NCC-associated epilepsy prevalence. Epilepsy was defined as ever having had more than one episode of unprovoked seizures. Medically confirmed cases of epilepsy had a computerized tomography (CT) scan of the brain before and after contrast medium injection. The diagnosis of NCC was made using a modification of the criteria of Del Brutto et al. (2001). KEY FINDINGS: Thirty-nine (4.4%) of 888 randomly selected villagers and 33 of 35 (94.3%) self-reported seizures cases were confirmed to have epilepsy by medical examination. Among the 68 participants with epilepsy who had a CT scan, 20 patients were diagnosed with definitive or probable NCC for a proportion of 46.9% (95% CI=30.2; 64.1) in Batondo and 45.5% (95%CI=19.0; 74.1) in Pabré. No cases of NCC were identified in Nyonyogo. SIGNIFICANCE: All the definitive and probable cases of NCC were from the two villages where pig breeding is common. Prevention policies intended to reduce the burden of epilepsy in this country should include measures designed to interrupt the life cycle of Taenia solium.